Fabrication of AA6016/(Al2O3 + AlN) hybrid surface composite using friction stir processing. (2020) - Nirmal Kumar, K.; Aravindkumar, N.; Eswaramoorthi, K.
Abstract: Friction Stir Processing (FSP) could be a new solid-state processing technique assisted by the Friction Stir Welding Principle (FSW), now commonly used in the manufacture of the metal surface composite due to its superior features. Composites are constructed materials consisting of two or more component materials with significantly different physical or chemical properties and remaining separate and distinct in the finished structure at a macroscopic level. The reinforcements impart their unique mechanical and physical properties for reinforcing the properties of the matrix. Since no fusion occurs during FSP, problems arise with liquid-solid interactions between the two reinforcing hard particles and removing liquid aluminium. This makes the FSP a potential fabrication tool for Al-MMC's. In various proportions, alumina and aluminum nitride powders were mixed and packed inside the groove made inside the aluminum plate. Designed and manufactured high carbon high chromium tool with a cylindrical pin with the threaded profile. The parameters considered for the FSP were rotational speed, axial load, and speed of power travel. The plates were then cleaned, and the specimens were also prepared in compliance with metallurgical specifications from FSPed plates. The metallurgical properties of treated AMMC's were measured by using optical microscopy. The specimen's micro hardness is measured using Vicker's Hardness machine. Thus the effect of varying the hardness composition of the reinforcement material was studied.